Temperatures leading to heat escape responses in Antarctic marine ectotherms match acute thermal limits - Morley, S. A.; Chu, J. W. F.; Peck, L. S.; Bates, A. E. (Frontiers in Physiology, 2022)
Thermal tolerance windows are key indicators of the range of temperatures tolerated by animals and therefore, a measure of resilience to climate change. In the ocean, where ectotherms are immersed, body temperatures are tightly coupled to environmental temperature and species have few options for thermoregulation. However, mobile species do have the ability to orientate towards optimal temperatures and move away from sub-optimal or dangerous temperatures. Escape responses are one such locomotory behavior, which typically manifests as a series of violent flicking movements that move individuals out of dangerous environments. We tested 11 species of Antarctic marine ectotherms, from one of the most stable shallow water marine environments, with an annual temperature range of -2 to +2°C, that are vulnerable to small degrees of warming. Three species, the clam Laternula elliptica, the sea cucumber Cucumaria georgianus and the brittlestar Ophionotus victoriae, showed no, or virtually no, escape response to temperature. Escape responses from a further eight species had a median response temperature of 11.2 (interquartile range, 10 to 15.7°C), which is well above current environmental temperatures but close to the range for acute lethal limits of Antarctic marine ectotherms (range, 17.2 to 26.6 °C). This highlights that both acute tolerance limits and escape responses, fall outside current environmental temperatures, but also those predicted for 100s of years in the Southern Ocean. In a warmer Southern Ocean Antarctic fauna may not have the capacity to use temperature to select optimal thermal conditions, which leaves adaptation as a primary mechanism for their persistence.